2004
DOI: 10.1182/blood-2003-08-2841
|View full text |Cite
|
Sign up to set email alerts
|

Value of sequential monitoring of left ventricular ejection fraction in the management of thalassemia major

Abstract: Regular monitoring of left ventricular ejection fraction (LVEF) for thalassemia major is widely practiced, but its informativeness for iron chelation treatment is unclear. Eighty-one patients with thalassemia major but no history of cardiac disease underwent quantitative annual LVEF monitoring by radionuclide ventriculography for a median of 6.0 years (interquartile range, 2-12 years). Intraobserver and interobserver reproducibility for LVEF determination were both less than 3%. LVEF values before and after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 46 publications
11
135
0
2
Order By: Relevance
“…A retrospective analysis in deferoxamine-treated patients found that during a period of 15 years, maintenance of serum ferritins of 2500 mg/L was associated with estimates of improved cardiac-disease-free survival (Olivieri et al 1994). These findings were confirmed in subsequent studies, with lower ferritin concentration reported to predict even longer survivals (Telfer et al 2000;Borgna-Pignatti et al 2004a;Davis et al 2004). These findings should not be interpreted to suggest, in the day-to-day management of individual patients, that serum ferritin is an accurate assessment of body iron burden, although in clinical practice serum ferritin continues to be measured, usually at 6-mo intervals.…”
Section: Assessment Of Iron In Vivo Serum Ferritin Concentrationsupporting
confidence: 71%
“…A retrospective analysis in deferoxamine-treated patients found that during a period of 15 years, maintenance of serum ferritins of 2500 mg/L was associated with estimates of improved cardiac-disease-free survival (Olivieri et al 1994). These findings were confirmed in subsequent studies, with lower ferritin concentration reported to predict even longer survivals (Telfer et al 2000;Borgna-Pignatti et al 2004a;Davis et al 2004). These findings should not be interpreted to suggest, in the day-to-day management of individual patients, that serum ferritin is an accurate assessment of body iron burden, although in clinical practice serum ferritin continues to be measured, usually at 6-mo intervals.…”
Section: Assessment Of Iron In Vivo Serum Ferritin Concentrationsupporting
confidence: 71%
“…Iron-chelation therapy benefits thalassemia major patients both by reducing the iron-loading burden, and improving established iron-induced dysfunction within the heart [6,7]. The accumulation of iron in the heart is not inevitable provided that liver iron levels are controlled at all times, however once iron has accumulated in the heart, it is removed much more slowly by chelation therapy than liver iron [7], which can lead to a lack of correlation of liver and heart iron in previously chelated patients.…”
Section: Consequences Of Transfusional Iron Loading Thalassemiamentioning
confidence: 99%
“…Second, some patients died because cardiac symptoms and imaging evidence of ventricular dysfunction are late and ominous findings. 4 Whereas some patients could be "rescued" by continuous IV deferoxamine therapy, the process took several years and patients who refused to comply with long-term, intensive therapy (20%) died. 5 A third reason for continued cardiac mortality was that some older patients developed cardiac symptoms despite apparently adequate control of hepatic iron stores, suggesting insidious occult cardiac iron accumulation.…”
Section: Motivation For Mri Measurementsmentioning
confidence: 99%